Plastid encoded RNA polymerase activity and expression of photosynthesis genes required for embryo and seed development in Arabidopsis - Kremnev, Dmitry; Strand, Åsa (Frontiers in Plant Science, 2014)
Chloroplast biogenesis and function is essential for proper plant embryo and seed development but the molecular mechanisms underlying the role of plastids during embryogenesis are poorly understood. Expression of plastid encoded genes is dependent on two different transcription machineries; a plastid-encoded bacterial-type RNA polymerase (PEP) and a nuclear-encoded phage-type RNA polymerase (NEP), which recognize distinct types of promoters. However, the division of labor between PEP and NEP during plastid development and in mature chloroplasts is unclear. We show here that PRIN2 and CSP41b, two proteins identified in plastid nucleoid preparations, are essential for proper plant embryo development. Using Co-IP assays and native PAGE we have shown a direct physical interaction between PRIN2 and CSP41b. Moreover, PRIN2 and CSP41b form a distinct protein complex in vitro that binds DNA. The prin2.2 and csp41b-2 single mutants displayed pale phenotypes, abnormal chloroplasts with reduced transcript levels of photosynthesis genes and defects in embryo development. The respective csp41b-2prin2.2 homo/heterozygote double mutants produced abnormal white colored ovules and shrunken seeds. Thus, the csp41b-2prin2.2 double mutant is embryo lethal. In silico analysis of available array data showed that a large number of genes traditionally classified as PEP dependent genes are transcribed during early embryo development from the pre-globular stage to the mature-green-stage. Taken together, our results suggest that PEP activity and consequently the switch from NEP to PEP activity, is essential during embryo development and that the PRIN2-CSP41b DNA binding protein complex possibly is important for full PEP activity during this process.